Perbandingan Faktor-Faktor Yang Mempengaruhi Penggunaan Electronic-Know Your Customer (e-KYC) - Mr. Fitree Tahe; Maria Ulfah Siregar; Mohammad Farhan Qudratullah (JISKA (Jurnal Informatika Sunan Kalijaga), 2021)
There are many technological developments in banks, one of which is online transactions. To get these transactions, an account should be opened using the electronic know you customer (e-KYC) verification system at banks. This research wants to know the differences in the factors that influence behavioral intentions to use e-KYC at SCB (The Siam Commercial Bank) Thailand and Bank Mandiri Indonesia. This is a quantitative research using a survey. The researcher has prepared a questionnaire of 160 respondents: 80 for Bank Mandiri and 80 for SCB. The results indicate that the willingness of Bank Mandiri Indonesia’s respondents to use electronic identity verification services is influenced by smaller factors compared to SCB Thailand’s respondents. In total, all of the factors defined in this research is influenced the willingness.